Tingkat Keberhasilan Program Sustainable Farming in Tropical Asian Landscape (S-FITAL) Kakao Di Kecamatan Sabbang, Luwu Utara - Khusnul Khatifha; Muh Zainal S; Anggra Alfian (JURNAL AGRICA, 2023)
The North Luwu Regency is a significant cocoa-producing region in South Sulawesi, and the government recognizes cocoa as one of the country's leading commodities. Various programs have been implemented by the government, private sector, and communities to enhance cocoa quality and productivity. The Sustainable Farming in Tropical Asian Landscapes (S-Fital) program is one such initiative aimed at advancing cocoa plantations and promoting sustainable agricultural land management to improve global market competitiveness. The research examines individual farmer characteristics, program assistant roles, communication processes, and the S-FITAL program's success rate. The study used purposive sampling from November to December 2022, analyzing data through descriptive and correlational analyses via the Spearman rank test. The results indicate a positive correlation between individual characteristics, program assistant roles, communication processes, and program success. Farmers benefit from this research through improved companionship and communication processes.